Dietary indicators for assessing the adequacy of population zinc intakes - Hotz, Christine (SAGE Publications, 2007)
The assessment of dietary zinc intakes is an important component of evaluating the risk of zinc deficiency in populations, and for designing appropriate food-based interventions, including fortification, to improve zinc intakes. The prevalence of inadequate zinc intakes can describe the relative magnitude of the risk of zinc deficiency in the population and identify subpopulations at elevated risk. As a cornerstone to evaluating the adequacy of population zinc intakes globally, a set of internationally appropriate dietary reference intakes must be defined. The World Health Organization/Food and Agriculture Organization/International Atomic Energy Agency (WHO/FAO/IAEA) and the Food and Nutrition Board/US Institute of Medicine (FNB/IOM) have presented estimated average requirements (EAR) for dietary zinc intake, and, more recently, the International Zinc Nutrition Consultative Group (IZiNCG) presented a revised set of recommendations for international use. A prevalence of inadequate zinc intakes greater than 25% is considered to represent an elevated risk of population zinc deficiency. As the requirement estimates are derived from smaller, clinical studies and, for children, most components of the estimates are extrapolated from data for adults, it was desirable to evaluate their internal validity. The estimated physiological requirements for adult men and women appear to adequately predict zinc status as determined by biochemical indicators of status and/or zinc balance. With the use of data from available studies, the reported prevalence of low serum zinc concentration and the estimated prevalence of inadequate zinc intakes predict similar levels of risk of zinc deficiency, particularly among pregnant and nonpregnant women. Conformity between these two indicators is less consistent for children, suggesting that further data and/or direct studies of zinc requirements among children are needed.